Investigations on single-phase natural circulation loop dynamics. Part 3: Role of expansion tank. (January 2015) - Naveen, Kumar; Iyer, Kannan N.; Doshi, J.B.; Vijayan, P.K.
Abstract: Expansion tank is an important component of all single-phase natural circulation loops. The tank serves the twin purposes of venting the air out during the loop filling and accommodation of the swells and shrinkages of the loop fluid during the transient. In the present study, experimental investigations have been carried out in a rectangular single-phase natural circulation loop to bring out the role of expansion tank in loop dynamics. The results on loop stability and transient behavior are discussed. The experimental investigations show that there is significant amount of heat exchange between the main loop fluid and the expansion tank fluid. First, the results of experimental studies are presented. The different flow regimes observed in these experimental investigations are discussed. Next, a model is presented for taking into account the heat exchange between the main loop fluid and the expansion tank fluid. Finally, the model is applied to simulate the dynamic behavior of different single-phase natural circulation loops. The investigations carried out in this study have helped in resolving the issue of hysteresis observed in these loops. Highlights: Experimental and numerical investigations on expansion tank dynamics are reported. Investigations on natural circulation loop (NCL) performance are presented. Role of expansion tank in loop single-phase NCL dynamics has been investigated. A model has been proposed for expansion tank dynamics. Role of expansion tank in hysteresis observed experimentally is explained.